2021
DOI: 10.54530/jcmc.348
|View full text |Cite
|
Sign up to set email alerts
|

Family, Social and Organizational Support Among Healthcare Professionals During Covid-19 Pandemic in Selected Districts of Nepal

Abstract: Background: One of the important factors that could affect better health care delivery during COVID-19 pandemic remains the better working environment for healthcare professionals. Support provided by the family, society and workplace would play an important role to boost their work performance. This study aimed to assess the perception of family, social and organizational support among the frontline healthcare professionals during COVID-19 pandemic in selected districts of Nepal. Methods: This descriptive cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…These findings could guide organizations to take proactive measures to promote HCWs' health status and personal coping strategies (Rangachari & Woods, 2020; Sapkota et al, 2021). Supporting strategies should provide effective communication procedures, rewarding systems, job security, job‐life balance and self‐development opportunities (Alketbi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These findings could guide organizations to take proactive measures to promote HCWs' health status and personal coping strategies (Rangachari & Woods, 2020; Sapkota et al, 2021). Supporting strategies should provide effective communication procedures, rewarding systems, job security, job‐life balance and self‐development opportunities (Alketbi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, older HCPs may have more stable family dynamics. Indeed, older HCPs reported having the most support from family and friends during the COVID-19 pandemic (36). In addition, the QoS of older female HCPs might be better because, due to their older ages, their sleep may no longer be affected by pregnancy and breastfeeding, which were the explanations provided by some female HCPs (26,33).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the support for health professionals from the organizations they work for during the COVID 19 process was lower than that from their families and the community. Organizational support plays an important role in the work motivation of health workers (Sapkota et al., 2021 ). Support from medical institutions decreases the intention to resign (Kusui et al., 2017 ), and supportive managers have a positive effect on the emotional status of health professionals (Greenberg et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%